Healing beyond bone: a qualitative study of the core decompression experience of physically active patients with stage II hip avascular necrosis - Mehmet Yiğit Gökmen; Habibe Sevim Gökmen; Mesut Uluöz; Özhan Pazarcı; Alaaddin Levent Özgözen; Ender Ali Uluç; Osman Çiloğlu (Journal of Orthopaedic Surgery and Research, 2025)
Abstract Background Avascular necrosis (AVN) of the femoral head is a degenerative condition characterized by ischemic bone death, resulting in pain and impaired mobility. Core decompression, a surgical intervention, is widely performed for stage II AVN to alleviate symptoms and delay disease progression. While clinical and radiological outcomes are well-documented, the psychosocial dimensions of recovery remain underexplored. This study aims to understand the experiences of physically active patients diagnosed with stage II AVN who have undergone core decompression surgery during their follow-up period, allowing for a broader evaluation of the experiences of this patient group. Methods This study used semi-structured interviews, in-depth follow-up questions, and thematic analysis to explore the experiences of physically active patients who underwent core decompression surgery for stage II AVN of the femoral head. The participants were assessed 1–3 years post-surgery. Conducted in the Orthopaedics and Traumatology outpatient clinic of Adana City Training and Research Hospital, the study included 31 patients who had core decompression surgery between January 2020 and January 2024, with at least one year of follow-up data. Data collection, including demographic and qualitative information, was carried out during the first week of April 2024, followed by the member-checking process in the third week. A thematic analysis checklist and COREQ guidelines were used to ensure analysis reliability. Results The experiences of 31 patients (mean age 37.19 ± 8.21 years, 12 females, 19 males) were summarized into five main themes that emerged from the data analysis process: ‘Expectations and Concerns Before Surgery,’ ‘Postoperative Physical Experiences,’ ‘The Psychological and Emotional Process,’ ‘Social Support and Family Relationships,’ and ‘Health Services and Medical Support.’’ Twelve sub-themes emerged from the main themes. Conclusions Core decompression offers significant benefits to patients with stage II AVN by improving mobility and reducing pain. However, psychological support, patient education, and robust social networks are essential to address the holistic needs of recovery. These findings highlight the importance of integrating patient-centered approaches into surgical care to optimize outcomes and satisfaction. Further qualitative research is needed to explore the experiences of AVN patients at different stages to inform multidisciplinary care strategies.